Bioresorbable Nonwoven Patches as Taxane Delivery Systems for Prostate Cancer Treatment - Joanna Jaworska; Arkadiusz Orchel; Anna Kaps; Marzena Jaworska-Kik; Anna Hercog; Mateusz Stojko; Jakub Włodarczyk; Monika Musiał-Kulik; Małgorzata Pastusiak; Marcelina Bochenek; Marcin Godzierz; Janusz Kasperczyk (MDPI AG, 2022)
Prostate cancer is the second most common cancer in males. In the case of locally advanced prostate cancer radical prostatectomy is one of the first-line therapy. However, recurrence after resection of the tumor can appear. Drug-eluting bioresorbable implants acting locally in the area of the tumor or the resection margins, that reduce the risk of recurrence would be advantageous. Electrospinning offers many benefits in terms of local delivery so fiber-forming polyesters and polyestercarbonates which are suitable to be drug-loaded were used in the study to obtain CTX or DTX-loaded electrospun patches for local delivery. After a fast verification step, patches based on the blend of poly(glycolide-ε-caprolactone) and poly(lactide-glycolide) as well as patches obtained with poly(lactide-glycolide- ε-caprolactone) were chosen for long-term study. After three months, 60% of the drug was released from (PGCL/PLGA) + CTX and it was selected for final, anticancer activity analysis with the use of PC-3 and DU145 cells to establish its therapeutic potential. CTX-loaded patches reduced cell growth to 53% and 31% respectively, as compared to drug-free patches. Extracts from drug-free patches showed excellent biocompatibility with the PC-3 cell line. Cabazitaxel-loaded bioresorbable patches are a promising drug delivery system for prostate cancer therapy.